A model-based framework for increasing the interdisciplinary design of mechatronic production systems. (2nd November 2018) - Kernschmidt, Konstantin; Feldmann, Stefan; Vogel-Heuser, Birgit
ABSTRACT: Over the past years, the design of production systems has changed rapidly towards complex mechatronic systems, tightly integrating mechanics, electronics and software. The development of such integrated systems requires new approaches to cope with this challenge in order to ensure the desired design and functionality of the system. This article analyses how the required information from different disciplines can be handled appropriately by the engineers. Therefore, a model-based framework is presented, which supports the interdisciplinary development process. It is based on the modelling language SysML and enables the integration of standardised properties through model libraries. Furthermore, the resulting model from the development phase can be used to analyse possible interdisciplinary impacts in the case of required changes. A case study is presented to evaluate the applicability of the proposed framework.